The Medical Committee's Implementation of Hospital Internal Regulations to Improve Hospital’s Clinical Governance - Pasrah Kitta; Indar Indar; Sabir Alwi (Syntax Corporation Indonesia, 2022)
The hospital is a complex organization that regulates many things and has a high risk. Thus it requires rules that become the basis and guidelines for running medical services. The regulation is Hospital by Laws, an internal hospital regulation that includes internal corporate regulations and internal regulations for medical staff, which are compiled based on the conditions and needs of the hospital. Hospital by Law is an important legal instrument to improve good clinical governance carried out by the medical committee. However, there are obstacles to its implementation, especially in applying Hospital by Laws in several hospitals. This study aims to determine the application of Hospital Laws and the role of the medical committee in improving good clinical governance. This research was conducted using an empirical approach by discussing legal symptoms' social aspects. The analytical method is a qualitative analysis by analyzing data collected from interviews with several respondents and secondary data in legal literature. The results showed that Hospital by Laws in the three (3) hospitals studied had not been implemented optimally. It is indicated by the low level of understanding of the hospital stakeholders about Hospital Laws. In addition, it was found that to improve good clinical governance, the medical committee has not been able to carry out its role optimally.